Forest Multiplication: A Game Based Learning Apps to Enhance Learning Experience in Multiplications for Primary Students towards 21st Century Learning Skills - Mohamed Ali, Mohd Hatta; Jasmi, Nurul Irvina Nabilah; Khalip, Nur Atikah; Hamdi, Haleeda Nornabiha; Jofri, Muhammad Hanif; Mohamed, Juliana; Abdul Hamid, Mariam (Multidisciplinary Applied Research and Innovation, 2020)
Nelson Mandela once said, education is a powerful weapon to change the world. The power of education extends beyond the development of skills that we need for economic growth. By having numbers of scientists, engineers, technologist, doctors and other professionals it will helps the nation to prosper. Thus, early education in science, techonology, engineering and mathematics are important and is the answers for a better nation in the future. Mathematical subjects are important subjects in producing a competitive generation in the science and technology fields [1]. From interviews, questionaires and observation, most of the primary school students have difficulties and lost motivation on learning mathematics esspecially in multiplication operations. Thus, the objective of this study is to investigate the problems on learning mathematics for the primary school students and propose a solutions to enhance their learning experience in mathematics. In order to achieve the objectives, a study was made from respondents of from Sekolah Kebangsaan Taman Universiti, Mersing National School and  Sekolah Kebangsaan Bukit Badong. ADDIE model is the methodology that have been used to develop the solution which is a game based learning applications. Finally, this project has the big potential to be commercialised.